2004
DOI: 10.1158/0008-5472.can-04-1800
|View full text |Cite
|
Sign up to set email alerts
|

Proinvasive Properties of Ovarian Cancer Ascites-Derived Membrane Vesicles

Abstract: Malignant ovarian ascites are rich in cellular components, membranebound vesicles, and soluble proteins. This study focused on the structure of membrane-bound vesicles and their ability to promote invasion in cultured malignant ovarian epithelium. Membrane vesicles were derived from women with stage I-IV malignant ovarian ascites and from nonmalignant gynecologic ascites. Isolated vesicles were characterized by immunofluorescence and Western blot analysis. Using gel zymography for matrix metalloproteinase (MMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
181
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(195 citation statements)
references
References 19 publications
8
181
1
4
Order By: Relevance
“…Our findings, as well as those of other investigators, have demonstrated that membrane vesicles isolated from ovarian cancer patients' peripheral blood and malignant effusions appear to be identical, in terms of general protein composition and presence of specific marker proteins (Taylor et al 1980(Taylor et al , 2003Graves et al, 2004). However, to date, it is unclear whether the shed tumourderived membrane vesicles are the same or distinct from tumourderived 'exosomes.'…”
Section: Discussionsupporting
confidence: 73%
“…Our findings, as well as those of other investigators, have demonstrated that membrane vesicles isolated from ovarian cancer patients' peripheral blood and malignant effusions appear to be identical, in terms of general protein composition and presence of specific marker proteins (Taylor et al 1980(Taylor et al , 2003Graves et al, 2004). However, to date, it is unclear whether the shed tumourderived membrane vesicles are the same or distinct from tumourderived 'exosomes.'…”
Section: Discussionsupporting
confidence: 73%
“…The main reasons for the low survival rate of patients with ovarian cancer are caused by the lack of effective early detection and treatment, as well as the highly metastatic nature of the disease (Gardner et al, 1995). The pathogenesis of this disease involves widespread dissemination of malignant ovarian epithelium throughout the entire peritoneal cavity (Graves et al, 2004). Various proteolytic enzymes, including urokinase-type plasminogen activator (uPA) and matrix metalloproteinase (MMP)-2 and MMP-9, are suggested as critical mediators for ovarian cancer metastasis (Kobayashi et al, 1992;Moser et al, 1994;Young et al, 1996;Fishman et al, 1997Fishman et al, , 2001.…”
Section: Introductionmentioning
confidence: 99%
“…These data indicate that enhancement of a6 integrin and uPA/uPAR in ovarian cancer cells occurs specifically in the presence of ascites without affecting normal ovarian epithelial cell function. Proinvasive properties of ovarian cancer ascitesderived membrane vesicles have been reported recently (Graves et al, 2004).…”
Section: Discussionmentioning
confidence: 98%